THU0115 THE VALUE OF KL-6 AS A PREDICTIVE FACTOR OF ACUTE EXACERBATION IN PATIENTS WITH RHEUMATOID ARTHRITIS-ASSOCIATED INTERSTITIAL LUNG DISEASE. (2nd June 2020) - Tanaka, N.; Nishimura, K.; Waki, D.; Kadoba, K.; Yoshida, T.; Murabe, H.; Yokota, T.
Abstract : Background: Acute exacerbation (AE) is a life-threatening complication in connective tissue disease (CTD) associated interstitial lung disease (ILD) (CTD-ILD), including rheumatoid arthritis (RA). Although several risk factors for AE in CTD-ILD have been suggested, these are inconsistent. Krebs von den Lungen-6 (KL-6) is reported as a useful blood marker to detect severe CTD-ILD and RA-ILD, and serum KL-6 levels are significantly higher in patients with AE than in those without AE in RA-ILD patients [1]. However, the predictive value of KL-6 for AE in CTD-ILD or RA-ILD has not been completely confirmed. Objectives: To investigate the predictive factors for AE including initial serum KL-6 levels at RA-ILD onset and sequential changes of KL-6. We also examined the causal relationship between AE and mortality of RA-ILD patients. Methods: We retrospectively reviewed 115 patients with RA-ILD treated in our hospital between 2005 and 2019. Suspected drug-induced pneumonia cases or patients with other coexisting CTD were excluded. Cox regression analyses was used for univariate analysis to detect predictors of AE. Overall survival rate, respiratory-related deaths-free survival rate and AE-free survival rate were analyzed using the Kaplan-Meier method. P < 0.05 was considered statistically significant. Results: Among 115 patients, 29 patients (25.2%) developed AE and 32 patients (27.8%) died. The median follow-up period (IQR) was 57 (25.0-91.5) months, 57.4% were female and the mean age at RA-ILD onset was 72.2 ± 7.9 years old throughout the whole cohort. Among the AE group, methotrexate (MTX), tumor necrosis factor α inhibitor (TNFi) and non TNFi biological-DMARDs were used at AE onset in 10.7%, 0.0%, and 3.6% of patients, respectively. There was a significant difference of serum KL-6 levels at AE onset between AE group and non-AE group (1081.9 ± 624.7 vs 556.1 ± 285.6 U/mL, p < 0.001). Initial serum KL-6 levels at RA-ILD onset in AE group were higher than those in non-AE group, without a significant difference (648.9 ± 325.7 vs 523.7 ± 276.8 U/mL, p = 0.050). The optimal cut-off level of initial serum KL-6 to predict AE was 551 U/mL according to ROC analysis. In univariate analysis, the following factors were significantly associated with AE; usual interstitial pneumonia (UIP) pattern on HRCT at AE onset (Hazard Ratio [HR]: 2.18; 95% confidence interval [CI]: 1.02-4.61; p = 0.045), initial serum KL-6 > 551 U/mL at RA-ILD onset (HR: 2.46; 95%CI: 1.17-5.43; p = 0.018), increasing serum KL-6 levels > 10% before AE onset compared to the previous year (ΔKL-6 > 10%/year) (HR: 4.98; 95%CI: 2.17-11.84; p < 0.001). Initial serum KL-6 > 551 U/mL at RA-ILD onset and ΔKL-6 > 10%/year before AE were also significant prognostic factors for AE when we analyzed only in non-UIP patients (HR: 2.84; 95%CI: 1.15-7.35; p = 0.024, HR: 9.49; 95%CI: 3.02-36.25; p < 0.001, respectively). Conversely, median age at RA-ILD diagnosis, positive ratio of anti-CCP antibody, smoking habits, respiratory comorbidities, SDAI score, and therapeutics at both RA-ILD and AE onset had no significant associations with AE. Patients with initial serum KL-6 > 551 U/mL at RA-ILD onset and ΔKL-6 > 10%/year before AE had a significantly worse AE-free survival rate compared to others (p < 0.001). (Figure 1 ). Moreover, patients with AE had significantly lower overall survival rate (p < 0.001) and respiratory-related deaths-free survival rate (p < 0.001) than those without AE. Conclusion: Serum KL-6 levels at the disease onset and its sequential changes may be able to predict AE in the near future and support the early detection of AE in RA-ILD patients. References: [1]Sarcoidosis Vasc Diffuse Lung Dis. 2016 Oct 7; 33 (3):216-223. Disclosure of Interests: Nozomi Tanaka: None declared, Keisuke Nishimura Speakers bureau: Mitsubishi Tanabe Pharma Corporation. Pfizer Inc. Kyowa Kirin Co., Ltd. Chugai Pharmaceutical Co., Ltd. ONO PHARMACEUTICAL CO., LTD. Japan Blood Products Organization. Kissei Pharmaceutical Co., Ltd. Astellas Pharma Inc. AYUMI Pharmaceutical Corporation. Eisai Co., Ltd. DAIICHI SANKYO COMPANY. Norvartis AG. Bayer AG. Sanofi K.K., Daisuke Waki Speakers bureau: Mitsubishi Tanabe Pharma, AbbVie Inc, eisai Co, . Ltd, ONO PHARMACEUTICAL CO., LTD, Keiichiro Kadoba: None declared, Tomohiro Yoshida: None declared, Hiroyuki Murabe: None declared, Toshihiko Yokota: None declared